Social Empowerment of Women through Micro-enterprises: A Case Study of Parbat District of Nepal - Dhaubhadel, Sarita (Nepal Journal of Multidisciplinary Research, 2022)
An analysis of the impact of women-owned microenterprises on women's social empowerment in Parbat District is made in the current study, Social empowerment of women through micro-enterprises: a case study of Parbat District, Nepal. Women's social empowerment gives them the tools they need to be independent, self-sufficient and have a positive self-image to deal with challenging situations. Women should also be able to participate in development activities and the decision-making process. It is widely acknowledged that women's empowerment can be well paying strategy for overall economic and social development. This has profoundly impacted how women are assisted along a continuum from welfare to development. By assisting women in obtaining economic empowerment, micro enterprise backed by governmental or non-governmental programs contribute to the social empowerment of women. In this study, the freedom of movement and economic independence are used as criteria, while the social empowerment of women through microenterprise is used as a predictor variable. This purposive sampling-based quantitative research study involved 384 women micro entrepreneurs in the Parbat district. The statistical estimates and analysis are based on a data set of survey. The data set was statistically tested using standard SPSS software. Data analysis methods included descriptive and regression analysis. The findings showed that women who engaged in these endeavors experienced social empowerment. The study found that before and after participating in micro-enterprise, the overall average mean value of social empowerment was 1.61 and 2.68, respectively. Due to their involvement in microbusinesses, women's social empowerment increased. It reveals that the most significant change in social group involvement (2.82) was seen after participating in the micro-enterprise.